Economic Policy Uncertainty and Foreign Direct Investment in Nigeria: Evidence from Quantile Regression - Aina, A. L.; Joseph, A. I.; Oloyede, H. O. (NIU Journal of Social Sciences, 2025)
Nigeria has faced significant challenges in attracting Foreign Direct Investment (FDI), with economic policy uncertainty (EPU) emerging as a key deterrent. Persistent policy instability, regulatory inconsistencies, and macroeconomic volatility have created an unpredictable investment climate, discouraging foreign investors. Moreover, theoretical and empirical literature has been inconsistent in explaining the impact of EPU on FDI. Therefore, this study investigated the effect of EPU on FDI in Nigeria from April 2016 to June 2023, employing Quantile Regression and the VAR Granger Causality/Block Exogeneity Wald Test to analyze the relationship. The study concluded that EPU had a detrimental impact on FDI, particularly at higher quantiles, were increased uncertainty significantly reduced investment inflows. Additionally, exchange rate fluctuations dampened FDI, while strong GDP growth and increased domestic credit to the private sector were more effective in attracting investment. The causality test further confirmed that EPU Granger-caused FDI, reinforcing its role as a significant driver of investment trends in Nigeria. Based on these findings, the study recommended that the Nigerian government adopt predictable economic policies to create a more stable investment climate and implement sound macroeconomic strategies to stabilize the exchange rate, thereby improving Nigeria’s attractiveness to foreign investors. Keywords: Economic policy uncertainty, foreign direct investment, quantile regression, Nigeria